Flow cytometric evaluation of physico-chemical impact on Gram-positive and Gram-negative bacteria - Fröhling, Antje; Schlüter, Oliver K. (Frontiers in Microbiology, 2015)
Since heat sensitivity of fruits and vegetables limits the application of thermal inactivation processes, new emerging inactivation technologies have to be established to fulfil the requirements of food safety without affecting the produce quality. The efficiency of inactivation treatments has to be ensured and monitored. Monitoring of inactivation effects is commonly performed using traditional cultivation methods which have the disadvantage of the time span needed to obtain results. The aim of this study was to compare the inactivation effects of peracetic acid (PAA), ozonated water (O3) and cold atmospheric pressure plasma (CAPP) on Gram-positive and Gram-negative bacteria using flow cytometric methods. E. coli cells were completely depolarized after treatment (15 s) with 0.25 % PAA at 10 °C, and after treatment (10 s) with 3.8 mg l-1 O3 at 12°C. The membrane potential of CAPP treated cells remained almost constant at an operating power of 20 W over a time period of 3 min, and subsequently decreased within 30 s of further treatment. Complete membrane permeabilization was observed after 10 s O3 treatment, but treatment with PAA and CAPP did not completely permeabilize the cells within 2 min and 4 min, respectively. Similar results were obtained for esterase activity. O3 inactivates cellular esterase but esterase activity was detected after 4 min CAPP treatment and 2 min PAA treatment. L. innocua cells and P. carotovorum cells were also permeabilized instantaneously by O3 treatment at concentrations of 3.8 ± 1 mg l-1. However, higher membrane permeabilization of L. innocua and P. carotovorum than of E. coli was observed at CAPP treatment of 20 W. The degree of bacterial damage due to the inactivation processes is highly dependent on treatment parameters as well as on treated bacteria. Important information regarding the inactivation mechanisms can be obtained by flow cytometric measurements and this enables the definition of critical process parameters.